2019
DOI: 10.1080/10962247.2018.1549121
|View full text |Cite
|
Sign up to set email alerts
|

Spatial differences in ambient coarse and fine particles in the Monterrey metropolitan area, Mexico: Implications for source contribution

Abstract: The ambient air of the Monterrey Metropolitan Area (MMA) in Mexico frequently exhibits high levels of PM 10 and PM 2.5. However, no information exists on the chemical composition of coarse particles (PM c = PM 10-PM 2.5). A monitoring campaign was conducted during the summer of 2015, during which 24-hr average PM 10 and PM 2.5 samples were collected using high-volume filter-based instruments to chemically characterize the fine and coarse fractions of the PM. The collected samples were analyzed for anions (Cl-,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 79 publications
1
16
0
Order By: Relevance
“…Thus, the wind components from MERRA-2 were not incorporated into the NN model. According to the data extracted from MERRA-2, during most of the study period, the main components of PM2.5 were sulfates (33%) and OC (29%) (Figure 6), which were similar to the findings of Martínez et al According to the data extracted from MERRA-2, during most of the study period, the main components of PM 2.5 were sulfates (33%) and OC (29%) (Figure 6 [48] revealed that anthropogenic sources were typically associated with high contributions of SO 4 2− , OM, and BC. Secondary inorganic aerosols in the form of ammonium nitrates that were not reported by MERRA-2 were found to be important compounds in the MMA [81].…”
Section: Merra-2 and Ground-based Data: Comparisonssupporting
confidence: 84%
See 1 more Smart Citation
“…Thus, the wind components from MERRA-2 were not incorporated into the NN model. According to the data extracted from MERRA-2, during most of the study period, the main components of PM2.5 were sulfates (33%) and OC (29%) (Figure 6), which were similar to the findings of Martínez et al According to the data extracted from MERRA-2, during most of the study period, the main components of PM 2.5 were sulfates (33%) and OC (29%) (Figure 6 [48] revealed that anthropogenic sources were typically associated with high contributions of SO 4 2− , OM, and BC. Secondary inorganic aerosols in the form of ammonium nitrates that were not reported by MERRA-2 were found to be important compounds in the MMA [81].…”
Section: Merra-2 and Ground-based Data: Comparisonssupporting
confidence: 84%
“…In contrast to other Mexican cities that have improved their air quality, the average concentrations of PM 2.5 in the MMA increased by~5 µg m −3 between 2013 and 2015 [47]. In routine monitoring network, annual averages of PM 2.5 were found in the range of 20-34 µg m −3 , which exceeded the corresponding national air quality standards of 12 µg m −3 (annual average) [48]. Annual seasonal variations in the concentration of PM 2.5 were observed, in which the highest concentration was in winter, and the lowest concentration was in the first half of the fall season [49].…”
Section: Pm25 and Meteorological Data From Merra-2mentioning
confidence: 66%
“…The data distribution of the variables in the best dataset is shown in Figure 4. In general, PM 2.5 and the meteorological variables displayed behavior typical of the region [32,53]. The ground-based temperature (Figure 4a) increased from April to August.…”
Section: Model Selection and General Seasonal Variation Of The Relevant Variablesmentioning
confidence: 89%
“…Large amounts of atmospheric dust might result in high AOD values [69]. Mancilla et al (2019) [32] also reported that (NH4)2SO4 can contribute to as much as 54% of the total mass of PM2.5 in the MMA. According to Gao and Zhang (2014) [70], the extinction coefficient increases with increased SO2 −4 , therefore yielding larger AOD values, as it is the integral of the aerosol extinction coefficient.…”
Section: Seasonal Variation In the Model Performancementioning
confidence: 98%
See 1 more Smart Citation